Can saline irrigation improve the quality of tomato fruits? - Oliveira, Carlos Eduardo da Silva [UNESP]; Zoz, Tiago; Seron, Cassio de Castro; Boleta, Eduardo Henrique Marcandalli [UNESP]; Lima, Bruno Horschut de [UNESP]; Souza, Lucas Raoni Roel; Pedrinho, Denise Renata; Matias, Rosemary; Lopes, Cinthia dos Santos; Oliveira Neto, Sebastião Soares de [UNESP]; Teixeira Filho, Marcelo Carvalho Minhoto [UNESP] (Wiley, 2022)
This study aimed to investigate the effect of irrigation with saline water on fruit quality, yield, and plant nutrition of tomato (Lycopersicon esculentum Mill.) cultivars. Tomato cultivation was carried out under protected environment conditions in a double row system with drip irrigation performed according to the demand of the plants. Commercial fruit weight, commercial fruit number, fruit yield, absorption of Ca, N, P, S, K, and Mg were all affected by saline irrigation. The leaf Na concentration and the concentration of total phenolic compounds, total titratable acids, total soluble solids, vitamin C, carotenoids, and flavonoids in the fruits were favored from the increase in irrigation salinity. The Na+ causes a deficiency of Ca, which impairs seed formation in tomato fruits, as Ca is a structural element in the formation of the pollen grain. The Onix genotype had the highest yield, weight, and number of commercial fruits under control and moderate salt stress conditions. Saline water impaired nutrient absorption and improved tomato fruit quality. Under salt stress, tomato plants were able to absorb and translocate large amounts of Na+ to the shoot and even improved the organoleptic quality of fruits, increasing the content of carotenoids, flavonoids, vitamin C, total phenolic compounds, total soluble solids, and total titratable acids of tomato fruits. The clustering analysis was able to show the highest genetic dissimilarity between the group composed of Shanty, Maestrina, and Ipa 6 and the group with Sheena, Totalle, and Pizzadoro under salt stress conditions; also, it evidenced the greater stability of these genotypes.